Pengaruh Struktur aktiva, dan Return On Asset Terhadap Struktur Modal pada Perusahaan Kimia di Bursa Efek Indonesia - Mirwansyah Putra Ritonga; Mhd Zulkifli Hasibuan (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
on the capital structure of Chemical Companies on the Indonesia Stock Exchange (IDX) for the period 2015-2018 are as follows: Based on research conducted on 8 Chemical Companies listed on the Indonesia Stock Exchange (BEI) for the period 2015-2018, it can be concluded that Asset to Capital Structure. Based on research conducted on 8 chemical companies listed on the Indonesia Stock Exchange (IDX) for the period 2008-2011, it can be concluded that Return On Assets (ROA) has no effect on capital structure. Based on research conducted on 8 Chemical Companies listed on the Indonesia Stock Exchange (IDX) for the period 2015-2018, it can be concluded that there is an effect of Asset Structure and Return on Assets together on Capital Structure.